Ontology using for decision making in a competitive environment - Lytvyn, Vasyl; Oborska, Oksana; Vysotska, Victoria; Dosyn, Dmytro; Demchuk, Andriy (Lviv Polytechnic National University, 2018)
A method of decision making system elaboration in competitive environment based on ontological approach was developed. The models based on a hinged Boyd-Moore automaton. State machine loops are the stages Boyd and filling processes, ontology editing and a search of relevant knowledge ontology. Possible transitions between the states of the machine and transfer parameters between them were determined. For a quantitative modeling of decision support process in a competitive environment, mathematical support and methods of domain-specific ontology in the Boyd cycle (OODA – observation, orientation, decision, action) were elaborated. Thus, for the military at an “Observations” stage intelligence domain ontology determining of the strengths and weaknesses of the enemy. At the stage of “orientation”, ontological data are used for simulation of possible realizations of the battle and for optimal positioning of the forces. For “Resolution” stage, target distribution was developed using a method based on genetic algorithms, which helped to reduce the computational complexity of finding effective distribution targets. Ontology expertise based on descriptive logic is presented to increase the effectiveness of possible solutions.
Keywords: decision support system (DSS); ontology; knowledge database; Boyd cycle (OODA); observation; orientation; decision; action; genetic algorithms; expected value; probability